Backbone resonance assignment for the N-terminal region of bacterial tRNA-(N1G37) methyltransferase - Yan, Li (2021)
Bacterial tRNA (guanine37-N1)-methyltransferase (TrmD) is an important antibacterial target due to its essential role in translation. TrmD has two domains connected with a flexible linker. The N-terminal domain (NTD) of TrmD contains the S-adenosyl-l-methionine (SAM) cofactor binding site and the C-terminal domain is critical for tRNA binding. Here we report the backbone NMR resonance assignments for NTD of Pseudomonas aeruginosa TrmD. Its secondary structure was determined based on the assigned resonances. Relaxation analysis revealed that NTD existed as dimers in solution. NTD also exhibited thermal stability in solution. Its interactions with SAM and other compounds suggest it can be used for evaluating SAM competitive inhibitors by NMR.